1989
DOI: 10.1038/icb.1989.31
|View full text |Cite
|
Sign up to set email alerts
|

Genetically‐restricted effector molecules released by human lymphocytes in response to early pregnancy factor

Abstract: SummaryThe binding of early pregnancy factor (EPF) to lymphocytes stimulates the release of soluble effector molecules. Studies in mice have shown that it is these factors rather than EPF as such which are inhibitory in the T cell-dependent reactions, the adoptive transfer of contact sensitivity and the rosette inhibition test. Two factors have been identified: mEPF-Si (Mr ~15 000) is major histocompatibility complex (MHC)-restricted while mEPF-S2 (Mr ~55 000) is restricted to a locus (or loci) outside the MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the oviduct, during oestrus and early pregnancy, produces an inhibitor, 55 , 56 which modifies the response of EPF in the rosette inhibition test 54 . In its presence, higher concentrations of EPF are required to stimulate release of lymphokines by which the action of EPF in the rosette inhibition test and the delayed‐type hypersensitivity (DTH) reaction is mediated 57 , 58 . The range of concentrations over which EPF is able to affect lymphocytes is thus extended, suggesting a possible biological function for the inhibitor.…”
Section: Nature Of the Early Pregnancy Factor Molecule And Factors Afmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the oviduct, during oestrus and early pregnancy, produces an inhibitor, 55 , 56 which modifies the response of EPF in the rosette inhibition test 54 . In its presence, higher concentrations of EPF are required to stimulate release of lymphokines by which the action of EPF in the rosette inhibition test and the delayed‐type hypersensitivity (DTH) reaction is mediated 57 , 58 . The range of concentrations over which EPF is able to affect lymphocytes is thus extended, suggesting a possible biological function for the inhibitor.…”
Section: Nature Of the Early Pregnancy Factor Molecule And Factors Afmentioning
confidence: 99%
“…The immunosuppressive action of EPF is mediated through the sequential induction of lymphokines. Rolfe et al have described two lymphokines, EPF‐S 1 and EPF‐S 2 , induced from both human and mouse lymphocytes 57 , 58 , 85 . The activity of both factors is genetically restricted, a property that clearly distinguishes them from the inducing EPF, which is neither strain nor species restricted.…”
Section: Early Pregnancy Factor Induces Genetically Restricted Lymphomentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo , it suppresses the delayed‐type hypersensitivity (DTH) response 12 , 13 , prolongs skin graft survival time 14 and suppresses clinical signs of experimental autoimmune encephalomyelitis (EAE) 11 , 13 , the animal model of multiple sclerosis (MS). Suppression of the DTH response is induced by soluble mediators released from lymphocytes following EPF binding 15 , 16 . Thus, EPF displays the regulated production and pleiotropic function typical of many cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…The cell pellet PI, produced by incubation of spleen cells with pregnancy serum or its active consti¬ tuent EPF, after washing to remove the inducing stimulus, provides the ALS-enhancing effect measured by the bioassay (Morton et ai, 1976). Rolfe et al (1988Rolfe et al ( , 1989 have shown that, at this point, the active agents are soluble suppressor factors produced in response to pregnancy serum or EPF by a small population of cells in the spleen cell suspension. By incubating PI in HBSS alone for a further 0-5 h and collecting the subsequent supernatant S2, Orozco et ai (1990) and Clarke et ai (1990) removed the inducing signal (EPF) and collected suppressor factors and any soluble mediators produced in response to them.…”
Section: Discussionmentioning
confidence: 97%